Parental Satisfaction with The Quality of Life of Patients Aged 8-12 Years Old with Cleft Lip and Palate at the Tawanchai Center in Northeastern Thailand - Pakkasung, Yupin; Saothonglang, Kaweesak; Pisek, Poonsak; Chowchuen, Bowornsilp (Srinagarind Medical Journal, 2024)
Background and Objective: Patients with cleft lip and cleft palate, 8-12 years old is the period of oral preparation. Gum ridge bone grafting, orthodontics and early adolescence, which rely on the competence of the interdisciplinary team in providing treatment and cooperation of patients and parents The objective of this study was to assess satisfaction with the quality of life of parents and patients with cleft lip and palate. In order to use the results for further development of patient care. Methods: This cross-sectional study conducted among families with cleft patients aged 8-12 years old undergoing surgery at the Tawanchai Center. Period of study was 1 year between January-December 2022. The sample group consisted of 32 participants. Data collection involved general questionnaires and a satisfaction survey with 41 items across five aspects. The cronbach alpha coefficient of THAICLEFT QoL was determined to be 0.861. Data analysis utilized descriptive statistics including, percentages, means, and standard deviations. Results: The majority of patients (65.63%) were males. Patients with unilateral cleft lip and cleft palate were 62.50. %. The percentage of patients undergoing bone graft surgery was 96.88%. The patients were typically under the care of their parents (65.63%) and enrolled in the Universal Coverage Scheme/Beautiful Smile Beautiful Voice Project, with a participation rate of 93.75%. The satisfaction of the quality of life in five different aspects revealed that patients expressed moderate satisfaction in treatment expenses and psychosocial aspects, while demonstrating high satisfaction levels in medical treatment services and the impact on family. Conclusion: The parents of the patients were satisfied with five aspects of the quality of life, with three aspects rated as high and two aspects rated as moderate. The results of this study will be used to improve patient care for increasing satisfaction with their quality of life.